The Kronecker product and some of its physical applications - Fernández, Francisco Marcelo (2016)
In a typical introductory course on quantum mechanics the student has to face two quite different operator products. One of them leads to, for example, commutators and the uncertainty principle, and the other appears when one goes from a one-particle system to a multi-particle one. The latter gives rise to the direct or tensor product of operators and vector spaces, and to the Kronecker product of the matrix representations of the operators. We illustrate the practical utility of the Kronecker product by means of two spin systems commonly discussed in introductory courses on quantum mechanics and also by means of a simple model for the interpretation of the NMR signal produced by two interacting protons.